Listening at Night: Toward an Ethnography of So(m)niferous Media - Dittrich, Josh (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2022)
Drawing on ethnographic research with undergraduate students on their listening and sleeping practices, this essay develops a concept of “so(m)niferous media” to describe how listeners/sleepers use audio media to (re)mediate their experience of the night. The essay outlines key theoretical and practical affinities between sleeping and listening, taking a sociocultural approach to sleep informed by critical work in sound and media studies. Sleeping is reconceived as a sonically mediated, non-conscious experience of listening that participates ambivalently in the 24/7 logic of commodification outlined by Jonathan Crary and others. One unexpected finding of the ethnographic work is that many sleepers deliberately avoid obvious sound media products for sleeping (e.g., sleep playlists and podcasts, noise machines, “nature” sounds, binaural beats, etc) and seek out attention-grabbing social media content instead. Rather than lull themselves to sleep, listeners seem to want to engage their attention fully, while paradoxically shutting it down at the same time. So(m)niferous media thus seem to work directly on the attention of the listener, not the acoustic ambience of the sleeping space.